Antimicrobial and fluoride release capacity of orthodontic bonding materials - Erika Machado Caldeira; Amanda Osorio; Edna Lucia Couto Oberosler; Delmo Santiago Vaitsman; Daniela Sales Alviano; Matilde da Cunha Goncalves Nojima (University of São Paulo, 2013)
OBJECTIVE: The aim of this study was to evaluate the antimicrobial and fluoride releasing capacity of 3 bonding materials. MATERIAL AND METHODS: Thirty nine specimens with standardized surface smoothness and dimensions were prepared. The antimicrobial capacity of the materials against S. mutans, L. casei and C. albicans was evaluated by determining the percentage of growth inhibition of these microorganisms in an inoculated medium, obtained by optical density readouts on a spectrophotometer. The potential to interfere in microbial growth on the surface of the studied materials was observed by means of scanning electron microscopy (SEM). The fluoride release capacity in ultrapure water for 14 days was analyzed by means of ion chromatography. RESULTS: The PLUS group presented the highest percentage of microbial inhibition and the most contamination-free surface. The FUJI group presented the best fluoride release capacity. CONCLUSIONS: The TransbondTM Plus Color Change was the one that presented the best general behavior considering the evaluated aspects.